Formação docente e Projeto de Vida: memórias e narrativas para uma pedagogia do encontro - Silva, Henrique Souza da (2024)
Being a high school educator demands pedagogical competencies across various sciences, favoring a comprehensive formation of the individual, considering the complex and diverse current reality. In light of this, this research analyzed the intricate process of implementing the New High School (Brazil), which has Life Projects as the structuring axis of the curriculum. From this itinerary and attentive to the narratives of teaching experiences within the context of Full-Time State High Schools in the State of Sao Paulo, a question emerges: how could we redefine teacher education considering the structuring axis of the Life Projects curriculum? To address this complex question, it is pertinent to question the paradigm of change in the pedagogical process regarding the training of teachers working in high school. Therefore, the main objective of this research is to establish an epistemological bias of self-knowledge, reflection on subjectivity in concrete relation to reality, fostering within teachers' experiences a pedagogical integration of training, professionalism, and life project as a pedagogy of encounter. To achieve this, three specific objectives were established: the first focused on a study of the cultural paradigm of initial and ongoing teacher education. In a second analysis, it reflected on the integration of teacher education and life projects and all its implications for the exercise of teaching professionalism. The third point proposed redefining teacher education through the narratives of teachers and school administrators from Full-Time High Schools, correlating curriculum, life projects, and teaching professionalism as a pedagogy of encounter. In this sense, the proposed methodology for conducting this research is grounded in the theoretical conceptions of qualitative research. In its initial phase, this methodological journey carried out an exploratory bibliographic survey of the cultural paradigm of teacher education, integrating the concept of life projects. In a subsequent stage, it critically analyzed the documents related to the implementation of the New High School and the Full-Time High School Program of the State of Sao Paulo, the pedagogical political projects, and the designed curricula of the researched schools. In the third phase, semi-structured questionnaires were administered, and narrative interviews were conducted to better understand the articulation between initial and ongoing training and their interactions with the curriculum and life projects among the teachers. The research hypothesis revolves around life projects as a pedagogy of encounter, which presupposes establishing a pedagogical path between knowledge areas and life projects that contribute to teacher education, transforming socialized knowledge into a process of humanizing individuals who are prepared for life